Spermine Differentially Refines Plant Defense Responses Against Biotic and Abiotic Stresses - Seifi, Hamed Soren; Shelp, Barry J. (Frontiers in Plant Science, 2019)
Roles of the major polyamines (mPA), putrescine, spermidine and spermine (Spm), in various developmental and physiological processes in plants have been well documented. Recently, there has been increasing focus on the link between mPA metabolism and defense response during plant-stress interactions. Empirical evidence is available for a unique role of Spm, distinct from the other mPA, in eliciting an effective defense response to (a)biotic stresses. Our understanding of the precise molecular mechanism(s) by which Spm modulates these defense mechanisms is limited. Further analysis of recent studies indicates that plant Spm functions differently during biotic and abiotic interactions in the regulation of oxidative homeostasis and phytohormone signaling. Here, we summarize and integrate current knowledge about Spm-mediated modulation of plant defense responses to (a)biotic stresses, highlighting the importance of Spm as a potent plant defense activator with broad-spectrum protective effects. A model is proposed to explain how Spm refines defense mechanisms to tailor an optimal resistance response.